Welding effect on tensile strength of grade S690Q steel butt joint - Chen, Cheng (2020)
In this study, welding effects on the tensile strength of high strength steel butt joints were investigated experimentally and numerically. Two butt joints were fabricated by joining two 8 mm thick reheated, quenched and tempered S690Q high strength steel (HSS) plates together using Shielded Metal Arc Welding with different welding heat inputs. In the experimental study, post-welding microstructure and micro-hardness tests performed for the butt joints confirmed the existence of a soft layer within the heat-affected zone. The size of this soft layer increased when higher heat input was adopted. Subsequent coupon tensile tests showed that the tensile strength of the butt joints deteriorated with the increase of the welding heat input. In numerical study, a finite element (FE) simulation considering the non-uniform material properties heat-affected zone was implemented to complement the experimental study. Comparisons between experimental and numerical results were carried out for the temperature history curves, failure modes and stress-strain curves for the coupons manufactured from the butt joints. It was found that the proposed simulation method could reflect the influence of welding process on the tensile strength of the S690Q HSS butt joints tested in this study.